Healthy Living Starts with a Smile: Oral Health Promotion and Early Detection of Degenerative Diseases among Community Members - Oktaviana Zunnita; Nhadira Nhestricia; Ema Nilafita Putri Kusuma; Nina Herlina; Syifa Aulia; Rima Andara Riswandi; Siska Pratiwi Suherman; Regina Jasmine Ramadhani; Kartika Eka Paksi (Jurnal Pengabdian Masyarakat Inovatif, 2026)
Healthy living begins with maintaining oral health and preventing chronic diseases through early detection and lifestyle modification. Oral health problems and degenerative diseases remain major public health challenges in Indonesia. This community empowerment program aimed to improve community awareness regarding oral health and to conduct early screening for degenerative diseases among residents of RW 15, Pandu Raya Residential Area, Bogor. The program employed a participatory approach involving community representatives, security personnel, cleaning staff, and local administrators. Activities included oral health education, dental examinations, screening of blood pressure, blood glucose, total cholesterol, and uric acid levels, as well as assessment of participants’ knowledge regarding non-pharmacological management of degenerative diseases using a structured questionnaire. A total of 23 participants attended the program. Dental examinations revealed that 22 participants (95.65%) had dental caries, while 9 participants (39.13%) required root canal treatment. Screening results showed elevated cholesterol levels in 11 participants (47.83%), elevated blood pressure in 8 participants (34.78%), elevated blood glucose levels in 7 participants (30.43%), and elevated uric acid levels in 6 participants (26.09%). Participants generally demonstrated good to very good knowledge regarding non-pharmacological management of hypertension, diabetes mellitus, and hyperuricemia, although misconceptions regarding cholesterol management remained evident. The program successfully increased community awareness of oral health and highlighted the importance of early detection and lifestyle modification for preventing degenerative diseases.